Evaluating the Efficacy of a Novel Phytase Source - J. R. Flohr; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 350 nursery pigs (PIC 1050 barrows, initially 33.2 lb and 49 d of age) were used in a 21-d study to determine the aP release curve for a novel phytase product (Microtech 5,000, VTR Bio-tech Co., Guangdong, China). Pigs were randomly allotted to pens at arrival to the facility, and on d 0 of the trial pens were allotted to 1 of 7 treatments in a randomized complete block design. There were 5 pigs per pen and 10 pens per treatment. Pigs were fed corn-soybean meal-based diets formulated to 1.25% SID lysine. A single batch of the basal diet (0.12% aP) was manufactured and subsequently divided and used as the major ingredient in experimental diet manufacturing. Experimental diets were formulated to contain increasing available P supplied by either an inorganic source (0.12%, 0.18%, and 0.24% aP from monocalcium P) or from increased phytase (250, 500, 750, 1000 FTU/kg). Diets were analyzed for phytase using the AOAC method, and analyzed concentrations were lower than formulated. Diets formulated to contain 250, 500, 750 and 1000 FTU/kg had analyzed concentrations of 155, 335, 465, and 780 FTU/kg, respectively. On d 21, one pig per pen was euthanized and fibulas were collected to determine bone ash weight and percentage bone ash. From d 0 to 21, increasing P from inorganic P or increasing phytase resulted in increased (linear, P<0.01) ADG, improved (quadratic, P<0.02) F/G, and heavier (linear P<0.01) ending BW. Bone ash weight and percentage bone ash were increased (linear, P<0.01) with increasing inorganic P and increasing phytase. Response criteria, which remained in the linear portion of the quadratic phytase curve (ADG, bone ash weight, and percentage bone ash), were used to calculate aP release curves. When analyzed phytase values and percentage bone ash are used as the response variable, aP release percentage for up to 780 FTU/kg of Microtech 5,000 phytase can be predicted by the equation (y = 0.000002766761x - 0.000000002225x2 - 0.000201841391), where x is the phytase concentration in the diet (FTU/kg).
Keywords: nursery pig; phosphorus; phytase